2019
DOI: 10.1186/s13058-019-1187-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic signatures with contrast-enhanced magnetic resonance imaging for the assessment of breast cancer receptor status and molecular subtypes: initial results

Abstract: Background To evaluate the diagnostic performance of radiomic signatures extracted from contrast-enhanced magnetic resonance imaging (CE-MRI) for the assessment of breast cancer receptor status and molecular subtypes. Methods One hundred and forty-three patients with biopsy-proven breast cancer who underwent CE-MRI at 3 T were included in this IRB-approved HIPAA-compliant retrospective study. The training dataset comprised 91 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 35 publications
6
83
0
Order By: Relevance
“…Again, these numbers lie within the 95% CI of our models, differing strongest in prediction of ER (AUC 0.79 vs 0.67). Our results in differentiation of molecular subtypes also go in line with a previous publication by Leithner et al [29], revealing comparable results for the differentiation of luminal A from HER2-enriched, luminal B from triple-negative and superior results for distinguishing HER2-enriched from triple-negative cancers.…”
Section: Discussionsupporting
confidence: 93%
“…Again, these numbers lie within the 95% CI of our models, differing strongest in prediction of ER (AUC 0.79 vs 0.67). Our results in differentiation of molecular subtypes also go in line with a previous publication by Leithner et al [29], revealing comparable results for the differentiation of luminal A from HER2-enriched, luminal B from triple-negative and superior results for distinguishing HER2-enriched from triple-negative cancers.…”
Section: Discussionsupporting
confidence: 93%
“…They therefore concluded that CAD-CEDM can provide complementary information to radiologists, mainly by reducing the number of false-positive findings. In a different study from the same group, Danala et al [23] used the CAD scheme of CEDM images to classify breast masses. The authors used the segmentation results obtained from dual-energy subtracted images of a CEDM dataset of 111 breast lesions to build a multilayer perceptron machine learning system able to classify mass lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already reported the value of radiomics analyses of DCE-MRI, including the value of DCE-MRI morphologic and functional radiomic features to provide insight into individual genomic signatures, breast cancer molecular subtypes, and clinically used recurrence scores [7,[20][21][22][23]. There are fewer studies on the value of radiomics analyses of CEM; nevertheless, based on these limited studies, the results have been encouraging [23][24][25]. Recently, we reported preliminary results on the potential of CEM radiomics analysis of 100 patients in a larger-scale CEM-only study [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, researchers have used various approaches when applying MRI-based radiomic features in breast imaging, but most studies have focused on the differential diagnosis of breast lesions, the prediction of pathological characteristics, and response to neoadjuvant chemotherapy [15][16][17][18][19][20][21][22] . Recently, one study reported that a MRI-based radiomics signature was an independent predictor of DFS 12 .…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ which investigated the role of radiomics in differentiating breast cancer subtypes have also shown that radiomic features related to lesion shape contribute the most among other features when discriminating TNBC from other subtypes 19,23 . Interestingly, whereas one shape-related radiomic feature was selected in the aforementioned study from Park et al 12 , none of the shape-related features were selected in our study.…”
Section: Discussionmentioning
confidence: 99%